Gonococcal arthritis - Puszczewicz, Mariusz (Przewodnik Lekarza/Guide for GPs, 2007)
Gonococcal arthritis results from blood dissemination of Neisseria gonorrhoeae from mucosal infection. Clinical features include polyarthralgia, tenosynovitis, arthritis and skin lesions. Real arthritis occurs in less than 50% of cases. If disseminated gonococcal infection is likely, blood samples should be immediately plated on nonselective chocolate agar, and specimens from the urethra, endocervix, rectum and pharynx on selective Thayer martin medium. Mucosal cultures are positive in 80-90% of cases. Patients should be given third generation cephalosporin and doxycyclin for accompanied Chlamydia infection. The patient’s sexual partner (s) for 30 days prior to symptoms must be examined and treated too.